How can psychosomatic physicians contribute to behavioral medicine? - Yoshiuchi, Kazuhiro (Biopsychosoc Med, 2016)
In Japan, there is a unique clinical department, “Psychosomatic Medicine”, while there is not a department of behavioral science or behavioral medicine in medical schools. Although only eight medical schools have the department, psychosomatic physicians in the department have been involved with behavioral medicine. In the present manuscript, the author would like to introduce the contribution to behavioral medicine made by psychosomatic physicians in three aspects, education, clinical settings, and research, and propose some strategy for psychosomatic physicians to get more involved with behavioral medicine.